Experimental evaluation method of density suitability between bridging lost circulation materials and drilling fluid - Yili Kang; Ketao Hao; Chengyuan Xu; Kun Guo; Jie Zhou; Ruiheng Wang; Yao Xiao; Yunsong Xie (Petroleum, 2025)
Ultra-deep geological conditions are complex, often leading to leakage issues. As the depth increases during ultra-deep bridging lost-circulation operations, the varying settling velocities of different types of lost circulation materials (LCMs) lead to gravitational differentiation. This causes stratification of the LCMs, forming an unevenly dispersed system and reduced plugging efficacy. An experimental methodology is described for assessing the density suitability between LCMs and drilling fluids, which calculates the density suitability factor (DSF) by measuring the density of the plugging slurry at various locations after a designated resting period, ultimately evaluating its density suitability based on the DSF. Experimental results indicate that LCMs with lower densities demonstrate superior density suitability compared to those with higher densities. Smaller particle sizes (10–40 mesh) show better density suitability than larger ones (2–6 mesh). Fracture-plugging experiments validated this method, the plugging slurry composed of a good density suitability material, such as walnut shells, exhibited no notable gravitational differentiation after 2 h, achieving a maximum plugging pressure of 16.4 MPa with 88 mL of total volume loss. In contrast, the slurry formed with poorly density suitability materials, such as calcite, showed significant gravitational differentiation after 2 h, achieving only 9.6 MPa in maximum plugging pressure and a total volume loss of 96 mL. These findings highlight that LCMs with superior density suitability enhance plugging efficiency, highlighting the critical role of density suitability testing and the optimization of plugging formulations to improve the success of plugging operations.